1999
DOI: 10.19030/rbis.v3i4.5439
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology In The Undergraduate Accounting Curriculum

Abstract: This study examines the extent to which undergraduate accounting programs are integrating information technology (IT) across the curriculum. Based on responses from nearly 70 accounting programs, respondents believe that integrating IT into the curriculum is important, but (1) few departments have an IT policy, (2) coverage of general IT topics is minor to moderate, and (3) student usage of computer applications is fairly low. The main technical barriers to IT integration are inadequate lab personnel and conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They further argue that there are various issues which have to be taken into consideration to meet the challenges of the future. Hermanson et al (1999) examined the integration level of IT in the undergraduate accounting programs across the curriculum in the US universities. Results indicated that integrating IT into the accounting curriculum is important, while few departments have an IT policy, coverage of IT topics is minor to moderate and students' usage of computer applications is fairly low.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They further argue that there are various issues which have to be taken into consideration to meet the challenges of the future. Hermanson et al (1999) examined the integration level of IT in the undergraduate accounting programs across the curriculum in the US universities. Results indicated that integrating IT into the accounting curriculum is important, while few departments have an IT policy, coverage of IT topics is minor to moderate and students' usage of computer applications is fairly low.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, other studies have called for the necessity to integrate relevant IT subjects into the accounting curriculum (AICPA, 2010;Al-Khadash & Al-Beshtawi, 2009;Awayiga et al, 2010;Boyce, 1999;Burnett, 2003;J. Chen et al, 2009;Greenstein & McKee, 2004;Hermanson et al, 1999;International Federation of Accounting [IFAC], 1999;Kotb et al, 2019;G. Pan & Seow, 2016;Sledgianowski et al, 2017;Stoner, 2009;Warren, 1999;Wessels, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Given this increase in textual coverage, we would expect to observe greater coverage of database topics in the curriculum. Indeed, several recent studies indicate Systems professors are paying more attention to database topics, albeit some are only providing a conceptual overview (Hermanson, et. al.…”
mentioning
confidence: 99%